The effect of oral zonisamide treatment on serum phenobarbital concentrations in epileptic dogs - Mahon, Elizabeth; Marsh, Oliver; Uriarte, Ane; Stabile, Fabio (Frontiers in Veterinary Science, 2024)
Zonisamide is used in dogs for the treatment of epileptic seizures. It is predominantly metabolised by CYP450 hepatic enzymes. When used concurrently with phenobarbital (PB), zonisamide clearance is increased and its elimination half-life decreases. However, the effect that zonisamide may have on serum PB concentrations in dogs has not been previously described. Eight dogs diagnosed with idiopathic epilepsy and two dogs with structural epilepsy commenced zonisamide at 8.0 mg/kg/12 h [7.4–10 mg/kg/12 h] following an increase in the frequency of epileptic seizures. Nine dogs were receiving PB every 12 h (4.2 mg/kg/12 h [3.8–6 mg/kg/12 h]), and one dog was receiving PB every 8 h (6 mg/kg/8 h). Following the addition of zonisamide and despite no increase in PB dosage, an increase in phenobarbital serum PB concentration was observed in 9 out of 10 dogs in subsequent measurements. In five dogs, phenobarbital serum concentrations were raised to concentrations higher than the reported hepatotoxic concentrations (trough>35 mg/L). This required a reduction in daily doses of PB. This case series suggests that zonisamide affects the metabolism of PB and causes an increase in PB serum concentrations over time.